Exploring students’ engagement in dramatizing proverbs: A study on collaboration, creativity, and communication - Tri Mulyaningsih; Eni Rosnija (Universitas Islam Negeri Ar-Raniry, 2026)
Despite the widespread recognition of drama-based activities as a pedagogical mechanism for promoting interactive language learning, empirical research examining student engagement in the dramatization of proverbs within English as a Foreign Language (EFL) context remains comparatively limited. This study investigates the nature of student engagement among sixth-semester English Language Education majors during proverb dramatization activities, with particular focus on three dimensions: collaboration, creativity, and communication. A qualitative-dominant mixed-methods design was employed to examine the factors influencing student engagement throughout the activity. Participants consisted of 31 students enrolled in a drama course. Data were collected through classroom observations, questionnaires, semi-structured interviews, and document analysis. Qualitative data were subjected to thematic analysis, while questionnaire responses were evaluated using descriptive statistics to complement and substantiate the qualitative findings. The results indicate that students demonstrated a high level of engagement across all three dimensions. With respect to collaboration, student engagement was strongly manifested in team-based cooperation and mutual support throughout the process of proverb dramatization. Regarding creativity, engagement was reflected in the development of contextually relevant scenarios and the use of symbolic interpretations of proverbs within student performances. Engagement in communication was evident through both verbal and non-verbal expressions, including pronunciation, intonation, gestures, and facial expressions. Furthermore, student engagement was influenced by a range of engagement enablers, such as peer support, personal motivation, and opportunities for creative expression, as well as several challenges, including time constraints, group coordination difficulties, and challenges related to idea development.